36 - 19w = -6w + 41
add -19w
add 6w
add 19w
add -36

Question

Asked 2/23/2012 7:56:20 AM

Updated 7/3/2014 10:57:00 AM

5 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by alfred123 [7/3/2014 10:56:53 AM]

trena99|Points 446|

xixu93|Points 85|

OxTornado007|Points 4028|

trena99|Points 446|

ramkitten|Points 7315|

OxTornado007|Points 4028|

dame016|Points 911|

Expert answered|eturker|Points 1571|

Question

Asked 2/23/2012 7:56:20 AM

Updated 7/3/2014 10:57:00 AM

5 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by alfred123 [7/3/2014 10:56:53 AM]

Rating

8

9(x - 2) = 18

9x -18 = 18

9x = 18 + 18

9x = 36

x = 36/9

x = 4

9x -18 = 18

9x = 18 + 18

9x = 36

x = 36/9

x = 4

Added 7/3/2014 10:46:07 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [7/7/2014 10:49:46 AM]

8

BA + C = D

BA = D - C

A = (D - C)/B

BA = D - C

A = (D - C)/B

Added 7/3/2014 10:47:25 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [7/7/2014 10:49:57 AM]

8

A = 3(B + C)

A = 3B + 3C

A - 3C = 3B

B = (A - 3C)/3

A = 3B + 3C

A - 3C = 3B

B = (A - 3C)/3

Added 7/3/2014 10:54:25 AM

This answer has been confirmed as correct and helpful.

8

5x - 6 = 4x + 8

5x - 4x = 8 + 6

x = 14

5x - 4x = 8 + 6

x = 14

Added 7/3/2014 10:54:51 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [7/7/2014 10:50:14 AM]

8

7x + 9 = 6x - 5

7x - 6x = -5 - 9

x = -14

7x - 6x = -5 - 9

x = -14

Added 7/3/2014 10:57:00 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [7/7/2014 10:50:23 AM]

The ability of solid rock to flow is called rigidity plasticity firmness flexibility

The ability of solid rock to flow is called PLASTICITY.

Question

Updated 10/14/2015 12:57:19 AM

1 Answer/Comment

The ability of solid rock to flow is called PLASTICITY.

Added 10/14/2015 12:57:19 AM

This answer has been confirmed as correct and helpful.

17x - 6 + 3x - 5 = x + 11 + 4x
20x - 11 = 5x + 11
20x + 1 = 5x + 11
9x = 16x **Weegy:** 20x-11=5x+11 **User:** 7(x - 3) = 4(x + 5)
x = 1/11
x = 1/3
x = 41/11
x = 41/3 **Weegy:** -8 **User:** Solve for x.
7(x - 3) = 4(x + 5)
x = 1/11
x = 1/3
x = 41/11
x = 41/3 **User:** Solve the following equation.
x + 6 = x + x
2
6
1472 **User:** An equation _____ has one solution.
always
sometimes
never **Weegy:** It's either a trick question, [ or the person who wrote the question is guilty of fuzzy thinking.
a linear (1st order) equation will have one solution
a quadratic (2nd order) equation will have two solutions
a cubic (3rd order) equation will have three solutions
...
an nth order equation will have n solutions.
An equation may have more than one solution, or the solution(s) may be complex, rather than real, but it will always have one solution - and sometimes more than one.
Had the question been "An equation _____ has only one solution", the answer would have been #2, "sometimes". ] **User:**
14 + 8m = 14 - 3m - 5m
Ø
{0}
{all reals} **Weegy:** Where are the following? These equation works out to zero. **User:** Solution set: Ø
-2m + 5 = 2m + 5
-2m + 5 = -2m + 5
-2m + 5 = -2m - 5 **Weegy:** -2m + 5 = -2m + 5 (More)

Question

Updated 7/3/2014 10:40:45 AM

3 Answers/Comments

7(x - 3) = 4(x + 5)

7x - 21 = 4x + 20

7x - 4x = 20 + 21

3x = 41

x = 41/3

7x - 21 = 4x + 20

7x - 4x = 20 + 21

3x = 41

x = 41/3

Added 7/3/2014 10:36:23 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [7/3/2014 3:25:48 PM]

x + 6 = x + x

x - x - x = -6

-x = -6

x = 6

x - x - x = -6

-x = -6

x = 6

Added 7/3/2014 10:37:15 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [7/3/2014 3:26:08 PM]

An equation SOMETIMES has one solution.

Added 7/3/2014 10:40:45 AM

This answer has been confirmed as correct and helpful.

33,127,192

questions answered

There are no comments.